GREEN BRAND EFFECTS ON GREEN PURCHASE INTENTION (LIFE RESTAURANT NEVER ENDED) - Rennyta Yusiana; Arry Widodo; Hidayat, Agus Maolana; Oktaviani, Prima Kusuma (Dinasti International Journal of Management Science, 2020)
Currently the restaurant business is growing rapidly in Bandung. This development occurred because of the support of people's behavior to eat outside the home. The issue of environmental damage such as global warming and the greenhouse gas effect, encouraging the emergence of restaurants that provide healthy products and green products. This restaurant appears in order to improve healthy behavior, reduce waste, and provide education to people to live healthy and to protect the environment. One of them is Restoran Kehidupan Tidak Pernah Berakhir (KTPB) which is a vegan restaurant in Indonesia that provides a healthy lifestyle by eating only vegetables and to educate consumers to consume green products. This study aims to determine the effect of Green Brand Positioning, Green Brand Knowledge, Attitude Toward Green Brand in increasing Green Purchase Intention. This research is a quantitative explanatory study using 400 community respondents. Bandung. The calculation and data processing will use Amos software. The results showed that, Green Brand Positioning has a significant impact on Green Brand Knowledge and has significant implications for change for Green Brand Attitude Towards and has a significant influence on Green Purchase Intention. Those variables have a significant impact on the Green Purchase Intention for consumers Kehidupan Tidak Pernah Berakhir Restaurants (KTPB).